Developing User Requirement’s Handbook for Malaysian Military Observers Using Phenomenology Approach - Su Emi Yusnita Wan Yusof, Wan; Zakaria, Omar; Zainol, Zuraini (International Journal of Engineering and Technology, 2018)
This paper attempts to show that application of phenomenology approach in developing the user requirementâ€™s handbook. This is the first study to document these phenomena in military used to gain their experiences for situational awareness. Therefore, the methodological approach taken in this study is a phenomenology approach. This paper will focus on Moustakasâ€™s approach because it has systematic steps started from identifying the phenomenon study until come out with the final output. Furthermore, this paper also aimed to show how the output obtained from this phenomenology approach, so the findings should make an important contribution to the field of peacekeeping. The final output is the result of data analysis procedure and guidelines for bringing together the textual and structural descriptions into appropriate table and will be apply for generating as a user requirement handbook.Â Â